2021
DOI: 10.48550/arxiv.2110.08875
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting the Performance of Multilingual NLP Models

Abstract: Recent advancements in NLP have given us models like mBERT and XLMR that can serve over 100 languages. The languages that these models are evaluated on, however, are very few in number, and it is unlikely that evaluation datasets will cover all the languages that these models support. Potential solutions to the costly problem of dataset creation are to translate datasets to new languages or use template-filling based techniques for creation. This paper proposes an alternate solution for evaluating a model acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 25 publications
(42 reference statements)
0
18
0
Order By: Relevance
“…However, in practice, one would like to understand the trade-offs before collecting the data. Recently, Srinivasan et al (2021) showed that it is possible to predict the zero-shot and few-shot performance of MMLMs for different languages using linguistic properties and their representation in the pre-training corpus. Understanding if there exists a similar dependence of the performance trade-offs with the linguistic properties of different languages can help us generalize our framework to the new languages without the need for explicit data collection.…”
Section: Discussionmentioning
confidence: 99%
“…However, in practice, one would like to understand the trade-offs before collecting the data. Recently, Srinivasan et al (2021) showed that it is possible to predict the zero-shot and few-shot performance of MMLMs for different languages using linguistic properties and their representation in the pre-training corpus. Understanding if there exists a similar dependence of the performance trade-offs with the linguistic properties of different languages can help us generalize our framework to the new languages without the need for explicit data collection.…”
Section: Discussionmentioning
confidence: 99%
“…We consider two different regression models to estimate the perfor-mance in our experiments. i) XGBoost: We use the popular Tree Boosting algorithm XGBoost for solving the regression problem, which has been previously shown to achieve impressive results on the task (Xia et al, 2020;Srinivasan et al, 2021).…”
Section: Performance Predictorsmentioning
confidence: 99%
“…Xia et al (2020) showed that it is possible to build regression models that can accurately predict evaluation scores of NLP models under different experimental settings using various linguistic and dataset specific features. Srinivasan et al (2021) (c) Number of multilingual tasks containing test data for each of the 106 languages supported by the MMLMs (mBERT, XLMR). The bars are shaded according to the class taxonomy proposed by Joshi et al (2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lauscher et al (2020) recently, showed that it is possible to predict the zero shot performance of mBERT and XLM-R on different languages by formulating it as a regression problem, with pretraining data size and typological similarities between the pivot and target languages as the input features, and the performance on downstream task as the prediction target. Along similar lines Srinivasan et al (2021) and Dolicki and Spanakis (2021) explore zero-shot performance prediction with a larger set of features and different regression techniques.…”
Section: Introductionmentioning
confidence: 99%